Secondary metabolite of Aspergillus oryzae impairs cell envelope integrity Klebsiella pneumoniae producing extended-spectrum beta-lactamase - Lailia Nur Rachma, Loeki Enggar Fitri, Sumarno Reto Prawiro, Tri Yudani Mardining Raras (Journal of Applied Pharmaceutical Science, 2023)
The defense system of Klebsiella pneumoniae producing extended-spectrum beta-lactamase (KPESBL) against the environment depends on the cell envelope and capsular polysaccharide (CPS). Its integrity depends on peptidoglycan-associated lipoprotein (pal), murein lipoprotein (lpp), and outer membrane protein A (ompA) covered by CPS. The outer membrane protects the cell envelope and serves as a siderophore entry-exit channel and membrane anchor for the CPS and fimbriae, crucial for K. pneumoniae pathogenicity. Here, we describe the effects of the secondary metabolite of Aspergillus oryzae (SMAO) on cell envelope integrity, cell adhesion, CPSs, siderophore, and KPESBL proliferation. The SMAO was exposed to the strain (KPESBL). Using quantitative real-time polymerase chain reaction, the expression of the pal, lpp, and ompA genes was assessed; CPS levels were measured using the Congo red binding assay (CR). Siderophore was measured using the chrome azurol sulphonate assay. Bacterial cell adherence was measured using the yeast agglutination assay. The growth curve was measured using the microdilution method. As validation, scanning electron microscopy was used to examine the structure of the cell membrane following exposure to SMAO. SMAO impairs the integrity of the cell envelope of KPESBL. Our research shows that SMAO may be a possible anti-infectious drug that breaks down the integrity of the cell envelope.